RISK MANAGEMENT OF INFORMATION SYSTEM IN DISKOMINFO STATISTIC AND ENCODING USING NIST SP 800-30 - Budi Tjahjono; Miri Ardiansyah; Gerry Firmansyah; Habibullah Akbar (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2023)
E-Government is a form of government service in digital form that utilizes the internet network which makes government services to the community easy. However, behind the perceived convenience, of course, there will be risks that arise, for example data loss, data theft, mis-access, illegal access, hardware damage, hacking, etc. which will have a negative impact on an organization, including in the Statistics and Encryption Communication and Information Service, XYZ Regency. The most commonly found threats are those that come from humans and electricity. In addition, there are still many sources of threats that have the potential to pose risks that will interfere with the implementation of electronic-based government. From the results of risk measurements that have been carried out based on NIST SP 800-30 By multiplying between the levels determined in the likelihood and impact processes to produce a number to be used as a guide in determining the level of risk, it was found that the risk threats originating from humans are 60% risk with Low level, 30% risk with Medium level, and 10% risk with High level. While the risk derived from electricity was 20% risk with Low level, 20% risk with Medium level, and 60% risk with High level. Lastly sourced from Technical is 34% risk with Low level, 33% Medium level risk, and 33% High level risk. Overall the risk assessment results were 39% risk threats with Low level, 33% risk threat with Medium level, and 28% risk threat with High level.